Effect of Rubber Compound Treatment and PTFE Extension Beam on Piezoelectric Energy Harvester Power Density / Mohd Sofwan Mohd Resali and Hanim Salleh - Mohd Resali, Mohd Sofwan; Salleh, Hanim (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Due to a number of advantages for small power applications (milliwatts), many researchers have begun to focus on usable energy harvesting from ambience. Over the years, to further expand the applications of vibration energy harvesting technology, many researchers have focused on how to improve the reliability and efficiency of the harvester. This paper presents work on improving piezoelectric energy harvesters based on structural modifications. Two different strategies of structural modification are proposed for optimization by using additional beam structure and additional rubber compound layer on the origin of the piezoelectric beam. This work summarizes the optimum performance of the strategies at a resonance frequency of 50±2 Hz at 0.25g ms-2 of acceleration. The parameters compared among the strategies are resonance frequency, voltage and power output. In general, the structural modification PZT-MER by clamped PTFE cantilever beam at the free end of piezoelectric and rubber compound gives the best power output of 2.87mW compared to PZT-ME (0.72 mW) and PZT-M (22μW).